Confirming the Reliability and Validity of the Sexual Minority Adolescent Stress Inventory in a National Sample of Sexual Minority Adolescents - Goldbach, Jeremy T.; Schrager, Sheree M.; Mamey, Mary Rose; Rhoades, Harmony (Frontiers in Psychology, 2021)
Objective: Sexual minority adolescents (SMA) experience numerous behavioral health disparities, including depression, anxiety, substance use, nonsuicidal self-injury, and suicidality. The primary framework to understand these disparities is minority stress theory, which frames this disproportionate burden as the result of discrimination, violence, and victimization in a homophobic culture. Empirical examinations of minority stress among SMA have been limited by lack of diverse samples or validated measures. This study engaged a national community sample of SMA to confirm reliability and validity of the Sexual Minority Adolescent Stress Inventory (SMASI). Method: A national sample of 2,310 SMA aged 14 to 17 was recruited in the United States through a hybrid social media and respondent-driven sampling approach. Item response theory and confirmatory factor analysis established the psychometric properties of the SMASI in this sample; minority stress was modeled as a latent variable in several regression models to verify criterion and divergent validity. Results: In this national sample (M age = 15.9; 64% female and 60% White), the factor structure of the SMASI and its 11 subscales was confirmed and shown to be invariant by demographic characteristics. Minority stress as measured by the SMASI was significantly associated with all mental and behavioral health outcomes. Conclusions: This study provides evidence that SMASI is a reliable, valid, and important tool for better understanding minority stress and subsequent health and mental health consequences among SMA.